Study on the role of the combination of quercetin and lutein in alleviating ulcerative colitis in mice - Xu, Zhiyue; Mi, Si; Chitrakar, Bimal; Wang, Liwen; Li, Yingxi; Shi, Renli; Sang, Yaxin; Yu, Wenlong; Wang, Xianghong (Frontiers in Nutrition, 2025)
IntroductionThis study aims to investigate the ameliorative effects and molecular mechanisms of combined quercetin and luteolin intervention on dextran sulfate sodium (DSS)-induced colitis in mice.MethodsBy establishing a DSS-induced colitis model, we systematically evaluated the comprehensive effects of the combined treatment on colonic histopathological damage, inflammatory cytokine expression, intestinal barrier function, and gut microbiota composition.ResultsThe quercetin-luteolin combination treatment group significantly ameliorated colon shortening, with colon length restored to 7.33 ± 0.09 cm (p < 0.05), reduced the severity of colonic ulcers, and decreased the disease activity index. The protective effects were manifested in two aspects: first, by synergistically upregulating the expression of tight junction proteins ZO-1, claudin-1, and occludin, the combined treatment maintained the functional integrity of the intestinal epithelial barrier; second, by inhibiting the PI3K/AKT/NF-κB signaling pathway, oxidative stress indicators were reduced by 52.6 and 20.2% (p < 0.05)., and the mRNA expression levels of inflammatory factors such as IL-1β, MyD88, P65, TNF-α, and TLR2 were downregulated. The expression level of AKT mRNA decreased by 69.5% (p < 0.05). In the LU + QR group compared to the IBD group. Additionally, the combined treatment reshaped the gut microbiota of colitis mice by modulating the relative abundances of Firmicutes, Bacteroidota, and Pseudomonadota.DiscussionUltimately, a synergistic alleviation model characterized by “inhibition of inflammatory pathways—restoration of barrier function—regulation of microbial homeostasis” was established. This study provides a theoretical foundation for the application of quercetin and luteolin in the treatment of colitis.